مساهمة البرامج التنموية للقطاع الفلاحي في تحقيق التنمية المستدامة في الجزائر - بدراني، محمد Badrani, Mohammed (مؤسسة كنوز الحكمة للنشر والتوزيع, 2013)
من خلال هذا المقال أردنا إلقاء الضوء على موضوع مهم ألا وهو موضوع التنمية المستدامة التي أصبحت كل الدول تسعى إلى تحقيقها، وسخرت لها كل الإمكانيات المادية والبشرية، والذي أكسب التنمية المستدامة هذه الأهمية هو الانعكاسات الايجابية لها على المجالات الاقتصادية والاجتماعية و البيئية وحتى الثقافية . \ كغيرها من الدول فقد سعت الجزائر إلى تحقيق التنمية المستدامة ، و ذلك من خلال البرامج التنموية التي أطلقتها ، و هي برامج الإنعاش الاقتصادي . \ من بين القطاعات التي أعطيت أهمية كبيرة من طرف الدولة القطاع الفلاحي، هذا القطاع الذي يمكن أن يساهم بشكل كبير في تحقيق التنمية المستدامة ، وقد جسدت مجهودات الدولة للنهوض بالقطاع الفلاحي في المخطط الوطني للتنمية الفلاحية والريفية، هذا المخطط الذي حاولنا من خلال هذه الورقة البحثية الوقوف على أهم توجيهاته، وأسس تطبيقه على أرض الواقع والنتائج المتحصل عليها أثناء تطبيقه و انعكاساته على الاقتصاد الوطني والوضع الاجتماعي والبيئة في الجزائر. Through this paper we want to shed light on an important topic not is the subject of sustainable development to which all states are seeking to achieve, and mocked her all human and material potentials, which earn sustainable development of this important is the positive repercussions on the economic and social spheres and environmental and even cultural. \ Like other countries Algeria has sought to achieve sustainable development, and through development programs launched by, and is the economic recovery programs. \ Among the sectors that has been given great importance by the state agricultural sector, a sector that can contribute significantly to the achievement of sustainable development, and has embodied the efforts of the state to promote the sector agriculture in the national plan for agricultural development and rural, this scheme, which we have tried through this paper stand on the most important research directions, and the foundations of its application on the ground and the results obtained during the application and its impact on the national economy and social situation and environment in Algeria.
Keywords: التنمية المستدامة -- الجزائر -- الزراعة -- البرامج التنموية -- الجوانب الاقتصادية -- المنتجات الغذائية